2020
DOI: 10.1111/apa.15229
|View full text |Cite
|
Sign up to set email alerts
|

Randomised simulation trial found an association between rescuers' height and weight and chest compression quality during paediatric resuscitation

Abstract: Aim Our aim was to examine the relationship between rescuers' anthropometric data and chest compression quality during paediatric resuscitation training. Methods This study focused on 224 medical students (53% women) who performed 2 minutes of paediatric resuscitation at the Medical University of Vienna, Austria: 116 on a baby manikin and 108 on an adolescent manikin. Skill Reporter software measured chest compression quality by recording compression depth, frequency, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…More specifically, the depth of chest compressions is higher in the overweight people compared with normal weight and underweight people. [19][20][21][22] To date, most researchers still mainly focused in their research on chest compression depth, rate and the chest compression-ventilation ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the depth of chest compressions is higher in the overweight people compared with normal weight and underweight people. [19][20][21][22] To date, most researchers still mainly focused in their research on chest compression depth, rate and the chest compression-ventilation ratio.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with earlier research examining the effect of BMI of participants on the quality of chest compressions: Chest compression depth in CPR is correlated with health care providers' body weight (and therefore often more muscle mass in the torso and/or arms). More specifically, the depth of chest compressions is higher in the overweight people compared with normal weight and underweight people 19‐22 . To date, most researchers still mainly focused in their research on chest compression depth, rate and the chest compression‐ventilation ratio.…”
Section: Discussionmentioning
confidence: 99%
“…I read with great interest the article by Bibl et al entitled ‘Randomised simulation trial found an association between rescuers’ height and weight and chest compression quality during paediatric resuscitation’ 1 . Differences in the quality of chest compression according to a rescuer's physical characteristics are an important issue because these differences could directly affect a cardiac arrest patient's outcome.…”
mentioning
confidence: 99%